John Curtin's War (vol. II): Triumph and Decline - Edwards, John (Random House Australia, 2018)
This second volume, 'Triumph and Decline', tells the full, fascinating story of the next four years, as Curtin leads Australia in meeting its enemy and its new friend, the latter personified by the charismatic, self-certain General Douglas MacArthur. As Churchill abandons Australia and pursues a 'Hitler first' strategy, Curtin and MacArthur fight to ensure that the War in the Pacific is an American priority. As the critical battles of the Coral Sea and Midway decide Australia's fate - and Kokoda creates a new legend - Curtin's resolute calm and implacable determination lift him beyond party conflicts to become 'Australia's leader'. But the outward strength disguises deteriorating health, and increasing doubt about the American alliance. Curtin determined Australia's future - but what would it have been had he lived?